Positively Framed Risk Information in Patient Information Leaflets Reduces Side Effect Reporting: A Double-Blind Randomized Controlled Trial. Issue 11 (25th January 2018) - Webster, Rebecca K; Weinman, John; Rubin, G James
Abstract: Background: Many medication side effects are the result of a psychologically mediated "nocebo effect, " triggered by negative expectations. Purpose: This study investigated if changing how side effect information is framed in patient information leaflets (PILs) reduces symptom reporting. Methods: A total of 203 healthy volunteers aged 18 or over were recruited from December 1, 2015 to December 5, 2016 into a double-blind randomized controlled trial carried out at the Clinical Research Facility at King's College Hospital. King's Clinical Trial Unit randomized participants (stratified by gender) to receive a PIL for "a well-known tablet available without prescription" that used standard side effect risk information (e.g., "Common, 1 in 10 people will be affected") or positively framed wording (e.g., "Uncommon, 90% of people will not be affected"). After reading their PIL, participants took the tablet (a placebo) and completed symptom reports 1 hr later. The main outcomes included the number of participants who attributed symptoms to the tablet, and the number and severity of attributed symptoms. Results: A total of 101 participants were assigned the standard PIL and 102 the positive framed PIL. Significantly more standard PIL participants attributed symptoms to the tablet ( n = 55, 54.5%) compared to positively framed PIL participants ( n = 40, 39.2%), odds ratio (OR) = 0.66, 95% CI: 0.46–0.93. Positive framing did not significantly reduce the total number ( p = .148) or severity ( p = .149) of symptoms attributed to the tablet. Conclusion: Positive framing reduced the likelihood of participants attributing nocebo-induced side effects to the tablet. Work is needed to assess the effectiveness in a patient population. Clinical Trial information: ISRCTN47470030 Abstract : Positively framing side effect risk in patient information leaflets reduces the number of people who report side effects after taking a sham tablet